2018
DOI: 10.7717/peerj.5127
|View full text |Cite
|
Sign up to set email alerts
|

Two sugar beet chitinase genes,BvSP2andBvSE2, analysed with SNP Amplifluor-like markers, are highly expressed after Fusarium root rot inoculations and field susceptibility trial

Abstract: BackgroundThe pathogens from Fusarium species can cause Fusarium root rot (RR) and other diseases in plant species including sugar beet (Beta vulgaris L.), and they have a strong negative impact on sugar beet yield and quality.MethodsA total of 22 sugar beet breeding lines were evaluated for the symptoms of RR after inoculation with Fusarium oxysporum Sch., isolate No. 5, and growth in a field trial. Two candidate genes for RR resistance, BvSP2 and BvSE2, encoding chitinases Class IV and III, respectively, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…phenylalanine ammonia-lyase (Ohl et al 1990 ), caffeic acid 3-O-methyltransferase, methylenetetrahydrofolate reductase 1 (Liu et al 2017 ), cell wall remodeling genes (basic 7S globulin, Yoshizawa et al 2011 ; alpha-glucosidase, Gillmor et al 2002 ; dirigent protein 22, Paniagua et al 2017 ) and stress response genes (glutathione S-transferase, Gullner et al 2018 ; pleiotropic drug resistance protein 1, Nuruzzaman et al 2014 ). Considering all DEGs downregulated in well storable varieties at T4 we found many more plant stress and defense related genes including six (endo)chitinase genes (Yerzhebayeva et al 2018 ) and nine WRKY transcription factors, some of them suggested to regulate stress responses (WRKY6, WRKY15) and others to regulate plants defense against pathogens (WRKY33, WRKY40, WRKY46; Bakshi and Oelmüller 2014 ). Further, we found 13 Germin-like proteins (GLP) that are known to have an oxalate oxidase function in sugar beet, which leads to the production of hydrogen peroxides, a second messenger molecule during plant stress responses (de los Reyes and McGrath 2003 ; Gutsch et al 2018 ) and six DIR proteins that are known to be plant stress-induced and may play a role in control over cell wall metabolism and/or production of antibacterial compounds (Paniagua et al 2017 ) (Table S5).…”
Section: Resultsmentioning
confidence: 95%
“…phenylalanine ammonia-lyase (Ohl et al 1990 ), caffeic acid 3-O-methyltransferase, methylenetetrahydrofolate reductase 1 (Liu et al 2017 ), cell wall remodeling genes (basic 7S globulin, Yoshizawa et al 2011 ; alpha-glucosidase, Gillmor et al 2002 ; dirigent protein 22, Paniagua et al 2017 ) and stress response genes (glutathione S-transferase, Gullner et al 2018 ; pleiotropic drug resistance protein 1, Nuruzzaman et al 2014 ). Considering all DEGs downregulated in well storable varieties at T4 we found many more plant stress and defense related genes including six (endo)chitinase genes (Yerzhebayeva et al 2018 ) and nine WRKY transcription factors, some of them suggested to regulate stress responses (WRKY6, WRKY15) and others to regulate plants defense against pathogens (WRKY33, WRKY40, WRKY46; Bakshi and Oelmüller 2014 ). Further, we found 13 Germin-like proteins (GLP) that are known to have an oxalate oxidase function in sugar beet, which leads to the production of hydrogen peroxides, a second messenger molecule during plant stress responses (de los Reyes and McGrath 2003 ; Gutsch et al 2018 ) and six DIR proteins that are known to be plant stress-induced and may play a role in control over cell wall metabolism and/or production of antibacterial compounds (Paniagua et al 2017 ) (Table S5).…”
Section: Resultsmentioning
confidence: 95%
“…In contrast to the Russian team, which used only the root tips for analysis, thus examining the local response, we decided to analyze the whole seedlings, which allowed us to recognize the systemic response of the plants to the infection. We decided to analyze two time points: 24h and 48h, because our goal was to learn the mechanisms activated in the initial stages of infection, these points were selected based on the previous analysis of chitinase gene expression, whose increase in time of Fol infection has been repeatedly confirmed both in the case of flax and other plant species [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Yerzhebayeva et al 60 discovered a significant correlation between two SNP markers, BvSP2 and BvSE2, and resistance to sugar beet root rot. In root rot-resistant breeding lines (2182, 2236, and KWS2320) inoculated with F. oxysporum, a remarkable increase in BvSP2 expression was observed after 14 days, reaching complete control levels by the 18th day of inoculation.…”
Section: Cercospora Leaf Spot Disease Resistancementioning
confidence: 99%